A Qualitative Study of Family Support Among Families Living in The Same Household With Tuberculosis Patients - Muhamad Rafly Bagus Nugrahanto; Makhfudli Makhfudli; Aria Aulia Nastiti (Universitas Pahlawan Tuanku Tambusai, 2026)
Family support for tuberculosis (TB) patients living in the same household plays a crucial role in treatment adherence and disease control, as families are directly involved in daily care, decision-making, and prevention of transmission. This study aimed to explore family support experiences among families living in the same household with TB patients. This qualitative study employed a descriptive phenomenological approach and involved 18 family members of TB patients receiving outpatient treatment at a primary healthcare center, selected using purposive sampling. Data were collected through in-depth semi-structured interviews and analyzed using Colaizzi’s method to identify key themes related to family support. The findings revealed six main themes: initial family perceptions of TB, family decision-making in treatment, forms of family support, efforts to maintain health and prevent transmission, barriers to supporting treatment, and family expectations regarding patient recovery. Families provided emotional, instrumental, and treatment-related support, despite facing psychological, social, and practical challenges. Family understanding of TB influenced their ability to support treatment adherence and implement preventive behaviors. Family support plays a central role in the TB treatment process, and strengthening family knowledge through education and continuous guidance from healthcare professionals is essential to enhance treatment success and prevent household transmission.